2013
DOI: 10.1021/jp4095112
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Bilayer Phase Transformations Detected Using Microcantilevers

Abstract: We report the use of microcantilevers to measure the phase transition temperature (T(m)) of supported lipid bilayers or lipid monolayers. During the solid-liquid phase transition, a supported lipid bilayer or monolayer undergoes a conformational change in which the lipid acyl chains transition from an ordered state to a disordered state. This process is accompanied by a free energy change, which is coupled to changes in the surface stress in the underlying solid support layer. These surface stress changes can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Initially, the SLB was formed on the coverslip by injecting a uorescent LUV solution (POPC with 0.5 mol% TR-DHPE) at a rate of 10 ml min À1 for 10 min into the microuidic channel using a syringe pump followed by PBS buffer to remove excess vesicles. Then, the triblock copolymer (F68 or F98) solution at a concentration of 100 mM was injected at various temperatures (25,30,35, or 40 C), followed by PBS buffer. The uidity of the lipids with and without the triblock copolymers was characterized by FRAP using confocal microscopy (Olympus IX81).…”
Section: Fluorescence Recovery Aer Photobleaching (Frap)mentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, the SLB was formed on the coverslip by injecting a uorescent LUV solution (POPC with 0.5 mol% TR-DHPE) at a rate of 10 ml min À1 for 10 min into the microuidic channel using a syringe pump followed by PBS buffer to remove excess vesicles. Then, the triblock copolymer (F68 or F98) solution at a concentration of 100 mM was injected at various temperatures (25,30,35, or 40 C), followed by PBS buffer. The uidity of the lipids with and without the triblock copolymers was characterized by FRAP using confocal microscopy (Olympus IX81).…”
Section: Fluorescence Recovery Aer Photobleaching (Frap)mentioning
confidence: 99%
“…The reason lies in the asymmetric environment of the SLBs. 25 The proximal leaet of the SLB is conned by a thin water layer and the solid support. The energy penalty for disrupting this connement is too great.…”
Section: Modeling the Lipid Diffusion Using A Free Area Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have focused on developing a basic understanding of polymer-membrane association mechanisms, using lipid bilayer systems as model membranes. [14][15][16][17][18][19][20][21][22][23][24] Cheng et al suggested that the hydrophobic PPO block inserts into the membrane interior whereas the hydrophilic PEO block weakly adsorbs onto the membrane surface. 14 Smallangle X-ray scattering experiments and coarse-grained molecular dynamic simulations indicate that the PPO block length is the key determinant for association with lipid membranes.…”
mentioning
confidence: 99%
“…Pure POPC liposomes were used as controls because phosphatidylcholine is one of the major components found in eukaryotic cell membranes and is widely used as the basic constituent in model membranes. [29][30][31][32] POPG, on the other hand, is a relatively minor component in eukaryotic cell membranes and is mostly found in bacterial cell membranes. 33 Nevertheless, given that POPG has the same phase transition temperature and almost the same chemical structure except for the headgroup as POPC, it can be considered as a simple model to study how the presence of net charge and hydroxyl groups affect membrane interactions with the copolymers.…”
Section: Introductionmentioning
confidence: 99%